2016
DOI: 10.1089/jpm.2016.0219
|View full text |Cite
|
Sign up to set email alerts
|

Physical Symptoms at the Time of Dying Was Diagnosed: A Consecutive Cohort Study To Describe the Prevalence and Intensity of Problems Experienced by Imminently Dying Palliative Care Patients by Diagnosis and Place of Care

Abstract: The terminal phase is perceived as a time where the majority will experience distressing symptoms, but this work suggests a contrary view. However, there did seem to be a detrimental effect depending on place of care with more significant problems recorded when people were dying at home. More work is needed to clarify this given the current push for more home deaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…The main conclusion was that the symptoms most likely to be bothersome for dying patients were shortness of breath and pain. More recently, the experiences of 18,975 dying patients under the direct or indirect care of hospice/palliative care services were examined with the significant majority of this group ( n = 14,238) dying of cancer [ 11 ]. Nearly 50% ( n = 5095) of this cohort had pain that was assessed as requiring attention (i.e., pain scores > 3) but only 4.4% were assessed as experiencing severe pain.…”
Section: Symptoms In the Terminal Phase Of Lifementioning
confidence: 99%
“…The main conclusion was that the symptoms most likely to be bothersome for dying patients were shortness of breath and pain. More recently, the experiences of 18,975 dying patients under the direct or indirect care of hospice/palliative care services were examined with the significant majority of this group ( n = 14,238) dying of cancer [ 11 ]. Nearly 50% ( n = 5095) of this cohort had pain that was assessed as requiring attention (i.e., pain scores > 3) but only 4.4% were assessed as experiencing severe pain.…”
Section: Symptoms In the Terminal Phase Of Lifementioning
confidence: 99%
“…An important role of PCOC is to report on this repository of prospectively collected information. Previously, PCOC researchers have found that palliative care services achieve statistically significant improvements in pain and other symptoms2 and have described symptom prevalence at the time dying is diagnosed 3. In those previous studies, the palliative care phase2 3 was the unit of counting with the outcome being the change from the beginning to the end of each phase.…”
mentioning
confidence: 99%
“…Despite continuing advances in the field of palliative care, symptoms such as pain and breathlessness remain at the forefront of the concerns of clinicians, patients and families [ 11 ]. Poorly controlled symptoms have been documented in patients with malignant and non-malignant conditions [ 35 37 ], which was reflected in this supplementary analysis.…”
Section: Discussionmentioning
confidence: 76%